An improving performance evaluation plot (PEP) for energy management in microchannel heat sinks by using nanofluids. (October 2020) - Yao, Peitao; Zhai, Yuling; Ma, Mingyan; Li, Yanhua; Wang, Hua
Abstract: Based on previous works, a performance evaluation plot (PEP) is presented to theoretically evaluate the techniques used in the determination of various thermophysical properties of fluids in energy saving. From it, PEP is divided into "three lines and four zones". Zone-1 indicates enhanced heat transfer without energy-saving, and enhanced heat transfer are in Zone-2, Zone-3 and Zone-4 with energy-saving for a fixed pumping power, pressure drop and flow rate, respectively. Then, microchannel heat sinks (MCHS) with cavities and different ribs arrangements were designed and simulated by using water-Al2 O3 nanofluids. Based on the estimation indicators of comprehensive thermal performance (PEP and the thermal enhancement factor η ), all working points located in the Zone-3 and 4 indicate that the increase in the heat transfer ratio is higher than that in the friction factor. The maximum enhancement of η is 2.2517 and it is measured in an odd-symmetric ribs structure (Channel D) with Reynold number equal to 582. The reasons are that the arrangement of odd-symmetric ribs continuously interrupts the development of the flow and thermal boundary layers. Moreover, cavities facilitate the full mixing of cold and hot fluids and reduce pressure drop.